Convective drying of squash (Cucurbita moschata): Influence of temperature and air velocity on effective moisture diffusivity, carotenoid content and total phenols (2017)
The influence of air temperature and air velocity on convection drying of pumpkin (Cucurbita moschata - UNAPAL Abanico 75) is studied using drying kinetics and changes in the content of total phenolic and carotene compounds. The response surface methodology was used to optimize the operating conditions for pumpkin pulp drying. The studied factors included drying temperature (45-65 °C) and air velocity (4 and 7 m.s-1). The optimum pumpkin pulp drying conditions were 55 °C and 7m.s-1 for the air temperature and velocity, respectively. The drying time was approximately 390 min. The flour had 6.34 ± 0.10% (db) for moisture, 141.5 ± 1.32 mg carotene/100g sample for total carotenoids and 72.9 ± 2.2 mg GAE/100g sample for total phenols.